Konstruksi Perundungan dan Solusinya dalam Al-Qur’an - Abdul Mutakabbir; Siti Nurjannah; Nuryani Nuryani (IAIN Bengkulu, 2022)
This paper attempts to describe the meaning and various forms of bullying. Specifically, it will display QS. QS. al-Hujurat/49:11 which describes three forms of bullying that often occur, both in public life, and through social media, such as insulting, making fun of, calling them awful names, intimidating, and even physical abuse. This type of research is qualitative with a literature review and a Qur'an approach. Based on several surveys, bullying occurs in almost all lines of life globally. The impact can damage a person's psychological and physical, even interfere with social to national and religious life. Therefore, it is necessary to pay more attention, starting from the government, officials, educators, society, and everyone. Thus, there needs to be a movement to minimize the safety of everyone who bullies as little as possible. The solutions offered in the Qur'an include providing children with moral education from an early age, teaching them to put forward good prejudices, always thinking before acting, and call by his name or a good nickname. The main thing is to instill awareness in everyone about the effects of bullying occurs, especially if you become a victim. The language of religion, everything you do will get the reward.